RIVER WATER DISCHARGE ANALYSIS IN PLTMH PLANNING - Inong Oskar; Frederik Palallo; Veronika Asri Tandirerung (Program Studi Pendidikan Teknik Mesin Fakultas Keguruan dan Ilmu Pendidikan Universitas Sriwiajaya, 2023)
Utilization of river water can be used as a renewable energy source through the construction of micro-hydro power plants. Bambalu village is flowed by the Bambalu river but the utilization of water has not been utilized as a renewable energy source, due to the unknown amount of water discharge. This study aims to determine how much the water discharge of the Bambalu river in the Kurra sub-district of Tana Toraja. This research method is to determine the water discharge by using the survey method by measuring the water velocity and cross-sectional area of the Bambalu river. The results showed that the average water flow velocity of the Bambalu river was 7.22 m /eti, while the width of the Bambalu River averaged 8.20 m, while the depth of the Bambalu river averaged 1.52m. Based on the theory of tringle section (triangular cross section), the cross-sectional area of 6,232 m2 was obtained, so that the average discharge of the Bambalu River was 44.99 m3 / second.